Gene panel analysis of literature-based infertility genes in Sertoli cell-only syndrome patients - Logara Klarić, Monika; Žunić, Lucija; Marić, Tihana; Trgovec-Greif, Lovro; Rokić, Filip; Merkler, Ana; Belužić, Robert; Vugrek, Oliver; Katušić Bojanac, Ana; Barbalić, Maja (Genetics & applications (Online), 2023)
Sertoli cell-only syndrome (SCOS) is a condition of male infertility characterized by a total absence of spermatogenic cells in nearly all seminiferous tubules. Apart from well-established genetic changes such as Klinefelter syndrome, CFTR variants, and Y-chromosome microdeletions, several hundred candidate genes were reported as associated with male infertility. We selected 92 evidence-based genes associated with infertility and investigated data from whole-exome sequencing in 6 individuals with clinically diagnosed SCOS. Eight heterozygous variants passed our filtering criteria, including population frequency ≤ 0.1% and high functional impact indicated by Sift, Polyphen, and CADD scores. Out of them, we considered only variants with putative autosomal dominant effects on infertility that were subsequently validated by Sanger sequencing. This filtering pipeline has led to the final likely causative variants detected in CHD7 and SCYP3 genes that potentially explain SCOS in two of our patients. Our discoveries suggest that gene panel testing of patients with SCOS could improve the diagnostic outcome; however, assembling a gene panel consisting of only genuine causative genes is crucial.